Hubungan Motivasi dan Hasil Belajar: Studi Pada Pusat Belajar Kegiatan Masyarakat Kota Ambon, Indonesia - Tutupary, Rosmarin; Emma Rumahlewang; John Rafafy Batlolona (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Low learning motivation is supported by socio-cultural factors, economics, parental education, and a lack of family support, affecting student learning outcomes. This study aims to analyze the relationship between motivation and learning outcomes of package C students at the Kadewa Dewa Community Learning Center (PKBM). This study is correlational. The population of the subjects of this study were all students registered at the Kadewa Dewa PKBM, Batu Merah Village, Sirimau District, Ambon City, consisting of 22 students of Package C class 10, 28 participants of Package C class 11 and 30 participants of Package C class 12, so the total number is 80 respondents. The sampling technique used proportionate stratified random sampling. The data analysis technique used quantitative analysis with Linear Regression inferential statistics using SPSS 16.00 for Windows software. The findings indicate that learning motivation contributes only 2% and 98% from other factors. Thus, there is no relationship between motivation and student learning outcomes. Therefore, the study provides educators with deep insight into exploring other factors influencing student motivation and learning outcomes. This study concludes that there is a significant relationship between the level of participant motivation and the achievement of learning outcomes. Participants with high intrinsic and extrinsic motivation tend to show better learning outcomes compared to participants with low motivation.